2014
DOI: 10.1055/s-0034-1372432
|View full text |Cite
|
Sign up to set email alerts
|

ALIF versus TLIF for Post-Discectomy Syndrome

Abstract: Both ALIF and TLIF techniques can be applied for PDS with equally good results. The technical advantages of ALIF have to be balanced with the additional morbidity and operation time owed to the additional approach. ALIF might be associated with a lower incidence of adjacent level disease compared with TLIF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Nevertheless, because the significance in MCID achievement differences were merely present in the weeks after surgery but not at 6 months and onward and mean PROMs did not differ at any time point, our results suggest that ALIF and TLIF isthmic spondylolisthesis patients will generally experience comparable outcomes in the months to years after fusion. The long-term MCID data provided from our analysis are consistent with the long-term clinical outcomes of Jacob et al 9 These results are also similar to those of Jägersberg et al, 29 in which both ALIF and TLIF cohorts markedly improved in pain scores, with no notable differences in pain between groups.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, because the significance in MCID achievement differences were merely present in the weeks after surgery but not at 6 months and onward and mean PROMs did not differ at any time point, our results suggest that ALIF and TLIF isthmic spondylolisthesis patients will generally experience comparable outcomes in the months to years after fusion. The long-term MCID data provided from our analysis are consistent with the long-term clinical outcomes of Jacob et al 9 These results are also similar to those of Jägersberg et al, 29 in which both ALIF and TLIF cohorts markedly improved in pain scores, with no notable differences in pain between groups.…”
Section: Discussionsupporting
confidence: 90%
“…3 The biomechanical properties and outcomes of various types of fusion were studied in several articles and it has been reported that interbody fusion from the anterior approach does not provide considerable benefits over transforaminal interbody fusion, nonetheless, the stability provided by ALIF cage was slightly higher. 14-16 According to the results of the regression analysis, application of a broad cage used for ALIF was associated with a significant decrease in the rate of screws loosening. A possible explanation of the observed effect is that cages applied for TLIF procedure provides support in the central part of the endplate, conversely broad cage provides load on periphery of endplate with greater compressive strength and distribution of load on greater surface, finally providing tolerance to the applied forces.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 It has been reported that the lack of the anterior support is a significant factor for pedicle screws loosening; however, the extent of the influence and the role of the applied fusion type remain undetermined. 14-16…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the posterior spinal structure and pedicles were preserved, this surgical technique may not hamper further surgery. Use of DLIF and lateral screws for ASD may be considered when multiple degeneration is present in the other spinal levels, and further ASD and re-revision surgeries could be expected, due to a lack of trauma to the posterior spinal structures 15) . A long-term follow-up study with a larger number of patients is required.…”
Section: Discussionmentioning
confidence: 99%